Cerebral 5-HT release correlates with [11C]Cimbi36 PET measures of 5-HT2A receptor occupancy in the pig brain. Issue 2 (February 2017) - Jørgensen, Louise M; Weikop, Pia; Villadsen, Jonas; Visnapuu, Tanel; Ettrup, Anders; Hansen, Hanne D; Baandrup, Anders O; Andersen, Flemming L; Bjarkam, Carsten R; Thomsen, Carsten; Jespersen, Bo; Knudsen, Gitte M
Positron emission tomography (PET) can, when used with appropriate radioligands, non-invasively generate temporal and spatial information about acute changes in brain neurotransmitter systems. We for the first time evaluate the novel 5-HT2A receptor agonist PET radioligand, [ 11 C]Cimbi-36, for its sensitivity to detect changes in endogenous cerebral 5-HT levels, as induced by different pharmacological challenges. To enable a direct translation of PET imaging data to changes in brain 5-HT levels, we calibrated the [ 11 C]Cimbi-36 PET signal in the pig brain by simultaneous measurements of extracellular 5-HT levels with microdialysis and [ 11 C]Cimbi-36 PET after various acute interventions (saline, citalopram, citalopram + pindolol, fenfluramine). In a subset of pigs, para-chlorophenylalanine pretreatment was given to deplete cerebral 5-HT. The interventions increased the cerebral extracellular 5-HT levels to 2–11 times baseline, with fenfluramine being the most potent pharmacological enhancer of 5-HT release, and induced a varying degree of decline in [ 11 C]Cimbi-36 binding in the brain, consistent with the occupancy competition model. The observed correlation between changes in the extracellular 5-HT level in the pig brain and the 5-HT2A receptor occupancy indicates that [ 11 C]Cimbi-36 binding is sensitive to changes in endogenous 5-HT levels, although only detectable with PET when the 5-HT release is sufficiently high.